Fine‐scale population genetic structure in a wide‐ranging carnivore, the leopard (Panthera pardus fusca) in central India. Issue 7 (31st December 2012) - Dutta, Trishna; Sharma, Sandeep; Maldonado, Jesús E.; Wood, Thomas C.; Panwar, H. S.; Seidensticker, John; Austin, Jeremy
Abstract Aim Habitat loss and fragmentation can influence the genetic structure of biological populations. Large terrestrial predators can often avoid genetic subdivision due to fragmentation because they have high rates of dispersal‐mediated gene flow. Leopards (Panthera pardus) are found in a variety of habitats and are the most widely distributed of the large and middle‐sized felids. We investigated the genetic diversity and population substructure of leopards (P.p fusca) in a fragmented meta‐population comprised of four populations from five protected areas and inter‐connecting corridors spread over an area of 45, 000 km2 in central India. Location Kanha, Pench, Satpura and Melghat Tiger Reserves, and interconnecting corridors in the Satpura‐Maikal Landscape of Central India. Methods We collected faecal samples and used genetic methods to identify individuals, estimate the genetic variation and evaluate the patterns of genetic substructuring within this meta‐population of leopards. Results We identified 217 individual leopards using a panel of seven microsatellite loci. Leopards showed high levels of genetic diversity in all sampled populations. Spatial and non‐spatial Bayesian analysis revealed at least two admixed genetic populations with indications of ongoing genetic subdivision. Genetic differentiation between populations was not explained by geographic distance. We identified nine individuals as migrants, most of which were assigned to reserves connected by corridors. Main conclusions Our study demonstrates that the leopard, an adaptable and vagile species, can become genetically differentiated with increased habitat fragmentation. Contrary to our hypothesis of panmixia, our results indicate that although leopards in this landscape are admixed, there is genetic substructuring at both the landscape and the fine‐scale level. We conclude that this is due to habitat fragmentation and corridors are of immense value in maintaining genetic connectivity in this landscape.